2022
DOI: 10.1111/ina.13088
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions for exhaled airflow from a cough with a surgical orN95mask

Abstract: Wearing surgical or N95 masks is effective in reducing the infection risks of airborne infectious diseases. However, in the literature there are no detailed boundary conditions for airflow from a cough when a surgical or N95 mask is worn. These boundary conditions are essential for accurate prediction of exhaled particle dispersion by computational fluid dynamics (CFD). This study first constructed a coughing manikin with an exhalation system to simulate a cough from a person. The smoke visualization method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 70 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that wearing masks could effectively reduce the number of droplets released into the air by the infection source and decrease the socialization distance to 0.5 m [12]. However, there are differences in filter efficiency and protective ability among the various types of masks on the market [13,14]. Researchers found that the survival rate of most bacterial particles in mask filtration layers (such as filter cores) can reach 44 to 77% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that wearing masks could effectively reduce the number of droplets released into the air by the infection source and decrease the socialization distance to 0.5 m [12]. However, there are differences in filter efficiency and protective ability among the various types of masks on the market [13,14]. Researchers found that the survival rate of most bacterial particles in mask filtration layers (such as filter cores) can reach 44 to 77% [15].…”
Section: Introductionmentioning
confidence: 99%